2007
DOI: 10.1007/s10661-006-9211-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of validamycin on some enzymatic activities in soil

Abstract: There have been few investigations of the possible effects of validamycin on the enzymatic activities in soil. The objective of this present work was to study the short-term influence of enzymatic activity in validamycin treated soils. The results showed that high dose of validamycin introduced into soil had an significant effect on soil enzymatic activities, the degree of inhibition or promotion of enzymatic activities was not only related to the concentration of validamycin, but also to the remain time. Comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 19 publications
2
18
0
Order By: Relevance
“…Application of pesticides decreases the urease activity in the soil which is beneficial for plants by reducing the hydrolysis of urea because it helps to maintain nitrogen availability to plant (Antonious 2003). On the other hand, the fungicides validamycin and Car enhanced urease activity, respectively, up to 13-21% and to 70% (Qian et al 2007, Yan et al 2011. In our experiment, we found inhibited urease activity by Gly and Imi whereas stimulated with Car.…”
Section: Discussionsupporting
confidence: 49%
“…Application of pesticides decreases the urease activity in the soil which is beneficial for plants by reducing the hydrolysis of urea because it helps to maintain nitrogen availability to plant (Antonious 2003). On the other hand, the fungicides validamycin and Car enhanced urease activity, respectively, up to 13-21% and to 70% (Qian et al 2007, Yan et al 2011. In our experiment, we found inhibited urease activity by Gly and Imi whereas stimulated with Car.…”
Section: Discussionsupporting
confidence: 49%
“…This study investigated the impact of BDE 209 on soil microbial activity and bacterial community composition, and found that the soil eco-system was indeed affected by BDE 209. Urease and Catalase have been widely used as indicators of the perturbation of soil by pollutants (Sahrawat 1979;Qian et al 2007). Parathion and Malathion inhibited urea hydrolysis by 30-61% after 0.5 weeks (Sahrawat 1979), and validamycin inhibited urease activity to 67.3% after 35 days incubation (Qian et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Because of their role as excellent indicators of soil microbial function and key components in nutrient cycling (Acosta-Martínez et al 1999;Belyaeva et al 2005), these enzymatic activities have been measured in studies assessing soil quality and management (Roldán et al 2005), and in studies examining the effects of pollutants on general soil processes and nutrient cycling (Tong et al 2007). The activity of urease is known to be sensitive to pollutants, such as heavy metals (Yang et al 2006), pesticides (Sahrawat 1979), and antibiotics (Qian et al 2007). Since catalase is an intracellular enzyme found in all aerobic bacteria and most facultative anaerobes, catalase activity in soils is considered to be a useful indicator of aerobic microbial activity, and has been found to be related to both the number of aerobic microorganisms and to soil fertility (García and Hernández 1997).…”
Section: Introductionmentioning
confidence: 99%
“…It is considered that heavy metals mainly inhibit enzymatic reactions through either complexing with substrate or blocking the functional groups of enzymes or reacting with complex enzyme substrate (Speir et al 1995). Soil enzymes might behave differently when exposed to a pollutant (Qian et al 2007). Liu et al (2007) reported a negative correlation between soil enzymatic activities and Pb and Cd contents in wastewater-irrigated soil, where soil catalase activity decreasing alongside with increasing dosages of Pb and Cd added to investigated soils.…”
Section: Resultsmentioning
confidence: 99%